Życie polityczne i wybory do Sejmu Ustawodawczego w 1947 r. w powiecie bialskim - Tarkowski, Paweł (Komunizm: System - Ludzie - Dokumentacja, 2023)
The first election to the Legislative Sejm after the Second World War in Poland took place on January 19, 1947. The ruling camp entered the election as the so-called Block of Democratic Parties, which comprised the Polish Workers’ Party, the Polish Socialist Party, the People’s Party, and the Democratic Party. The Polish People’s Party was the strongest opposition party with the greatest number of supporters among the public. The election was preceded by a fierce campaign, in which the Communists took all the available measures to win the election. The election campaign was conducted at the bidding of the security authorities, thus creating an atmosphere of terror. Political opponents were terrorized, persecuted, unjustly arrested, deprived of voting rights, or assassinated. The Communists won the election; this success, however, was possible only by means of rigging the results. It was the end of the political battle for power. The aim of this article is to present the political situation and the prevailing atmosphere among the people of Biała Podlaska County in the period that preceded the election, during the election, and in the first months after the election.